Self-Declared Oral Health Conditions and Oral Health-Related Quality of Life of the Brazilian Homeless Population: A Cross-Sectional Study - Karime de Castro Paiva; Lavínea Silva de Lima; Isabel Cristina Gonçalves Leite (Association of Support to Oral Health Research (APESB), 2022)
Objective: To associate the impact of oral health-related quality of life with socio-demographic determinants, self-perception, oral health conditions and access to dental treatment among homeless adults. Material and Methods: A cross-sectional study was carried out in a medium-sized Brazilian city in Minas Gerais. Socio-demographic data on the use of dental services and access to hygiene supplies for oral health were collected. Clinical aspects were collected by clinical observation using the Community Oral Health Indicator and oral health-related quality of life using the Oral Health Impact Profile (OHIP-14). Medians and interquartile distance were compared using the Mann-Whitney and Kruskal-Wallis tests. Multiple linear regression included significant variables (p<0.05) of the bivariate analysis according to each OHIP-14 domain. Results:Women had the lowest scores for the physical and social disability domains. Oral health conditions were associated with physical and psychological limitations and disability. The presence of more teeth was associated with a negative impact on the functional and physical domains, and inflamed gums, lack of need for dental prosthesis, and use of private services were associated with a greater psychological disability. Conclusion: Oral health-related quality of life of the homeless population is affected, especially in the physical and psychological aspects. Equitable and inclusive health actions aimed at this population should include oral health.